The effect of intravenous ferric carboxymaltose on health-related quality of life in iron-deficient patients with acute heart failure: the results of the AFFIRM-AHF study. (3rd June 2011) - Jankowska, Ewa A; Kirwan, Bridget-Anne; Kosiborod, Mikhail; Butler, Javed; Anker, Stefan D; McDonagh, Theresa; Dorobantu, Maria; Drozdz, Jarosław; Filippatos, Gerasimos; Keren, Andre; Khintibidze, Irakli; Kragten, Hans; et al.
Abstract: Aims: Patients with heart failure (HF) and iron deficiency experience poor health-related quality of life (HRQoL). We evaluated the impact of intravenous (IV) ferric carboxymaltose (FCM) vs. placebo on HRQoL for the AFFIRM-AHF population. Methods and results: The baseline 12-item Kansas City Cardiomyopathy Questionnaire (KCCQ-12), which was completed for 1058 (535 and 523) patients in the FCM and placebo groups, respectively, was administered prior to randomization and at Weeks 2, 4, 6, 12, 24, 36, and 52. The baseline KCCQ-12 overall summary score (OSS) mean ± standard error was 38.7 ± 0.9 (FCM group) and 37.1 ± 0.8 (placebo group); corresponding values for the clinical summary score (CSS) were 40.9 ± 0.9 and 40.1 ± 0.9. At Week 2, changes in OSS and CSS were similar for FCM and placebo. From Week 4 to Week 24, patients assigned to FCM had significantly greater improvements in OSS and CSS scores vs. placebo [adjusted mean difference (95% confidence interval, CI) at Week 4: 2.9 (0.5–5.3, P = 0.018) for OSS and 2.8 (0.3–5.3, P = 0.029) for CSS; adjusted mean difference (95% CI) at Week 24: 3.0 (0.3–5.6, P = 0.028) for OSS and 2.9 (0.2–5.6, P = 0.035) for CSS]. At Week 52, the treatment effect had attenuated but remained in favour of FCM. Conclusion: In iron-deficient patients with HF and left ventricular ejection fraction <50% who had stabilized after an episode of acute HF, treatment with IV FCM, compared with placebo, results in clinically meaningful beneficial effects on HRQoL as early as 4 weeks after treatment initiation, lasting up to Week 24. Graphical Abstract: